CAN PREECLAMPSIA BE PREVENTED AND MANAGED AT THE PRIMARY LEVEL OFCARE? - Guevara Ríos, Enrique (2025)
Hypertensive Disorders of Pregnancy (HDP), including preeclampsia, are among the leading causes of maternal and neonatal mortality worldwide, particularly in low- and middle-income countries. In Peru, preeclampsia is the second leading direct cause of maternal death. To address this issue, the National Institute of Health of Peru developed a Clinical Practice Guideline (CPG) in 2024 aimed at preventing and managing HDP at the primary care level. The guideline focuses on identifying pregnant women at risk based on clinical risk factors and recommends preventive interventions such as aspirin (100 mg/day) and calcium carbonate (1250 mg every 8 hours) starting in the second trimester. The guideline also advises against the use of antihypertensives in women without severe features and recommends urgent referral to higher-level facilities when preeclampsia is suspected. Developed using rigorous international methodologies (AGREE II and GRADE), this guideline aims to improve primary-level care, standardize management, and ultimately reduce maternal mortality in the country.